LEVERAGING INSTAGRAM FOR ELT: A SYSTEMATIC REVIEW - Mulia, Nova Agus; Dewanda, Zea Jelika; Tarihoran, Nafan (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
Instagram has emerged as a powerful tool in English Language Teaching (ELT), offering multimedia-based interactive learning experiences that enhance student engagement and instructional delivery. This systematic review examines the role of Instagram in ELT, highlighting its advantages, challenges and implications for language learning. Using the PRISMA method, 15 studies from various academic sources, including Google Scholar, and Mendeley, were analyzed. Findings show that Instagram encourages student participation through features such as Stories, Reels, and IGTV, supports peer collaboration, and facilitates formative assessment. However, challenges such as digital distractions, ethical concerns, and accessibility issues remain significant. This study concludes that while Instagram has the potential to revolutionize ELT, a structured implementation strategy is needed to maximize its benefits while overcoming its limitations. Future research should focus on developing best practices for integrating Instagram into the formal ELT curriculum to ensure its effectiveness as an educational tool.